2019
DOI: 10.1371/journal.pone.0222042
|View full text |Cite
|
Sign up to set email alerts
|

Reliable and robust method for abdominal muscle mass quantification using CT/MRI: An explorative study in healthy subjects

Abstract: BackgroundQuantification of abdominal muscle mass by cross-sectional imaging has been increasingly used to diagnose sarcopenia; however, the technical method for quantification has not been standardized yet. We aimed to determine an optimal method to measure the abdominal muscle area.MethodsAmong 50 consecutive subjects who underwent abdominal CT and MRI for possible liver donation, total abdominal muscle area (TAMA) and total psoas muscle area (TPA) at the L3 inferior endplate level were measured by two blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 40 publications
0
50
1
Order By: Relevance
“…These results may be attributable that the distance difference between GT and DLM was less than the height of a vertebral body, as the maximum distance difference was 40 mm. According to a recent study, the muscle area measurements were similar between the L2 inferior endplate level and L4 inferior endplate level 15 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These results may be attributable that the distance difference between GT and DLM was less than the height of a vertebral body, as the maximum distance difference was 40 mm. According to a recent study, the muscle area measurements were similar between the L2 inferior endplate level and L4 inferior endplate level 15 .…”
Section: Discussionmentioning
confidence: 83%
“…Still, these techniques have required manual selection of L3 slice CT images, which might be the greatest hurdle to achieve fully automatic body composition measurements. In general, it takes several minutes (around three minutes) to nd L3 slice level on abdominal CT even by experts 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The skeletal muscle area (SMA), (i.e., psoas, paraspinal, transversus abdominis, rectus abdominis, quadratus lumborum, and internal and external obliques) was identified by applying programmed thresholds (−29 to +150 Hounsfield units) [ 20 ]. The visceral and subcutaneous fat regions were defined by employing fat material thresholds (−190 to −30 Hounsfield units) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The measurements of skeletal muscle mass on CT and MRI were also found to be interchangeable. Park et al showed very good agreement between CT and MRI measurements of skeletal muscle mass at the level of the L3 vertebra (the ICC of reader 1 was 0.928 and that of reader 2 was 0.853) [ 64 ]. This result is also consistent with studies carried out at the level of the superior mesenteric artery (mostly the first lumbar vertebra) and the level of the third cervical vertebra (C3) [ 57 , 63 ].…”
Section: Considerations For the Radiologic Evaluation Of Sarcopenimentioning
confidence: 99%